Perilaku Konsumsi dalam Perspektif Ekonomi Islam: Telaah Terhadap Prinsip Maslahah - Yusrizal; Muhammad Yusuf Harahap; Rambe, M. Faiz Azhar; Siti Hajar Bahzar; Zakiah Rahmi Siagian (Jurnal Penelitian Ekonomi Akuntansi, 2025)
This article aims to examine consumption behavior from an Islamic economic perspective, focusing on the principle of maslahah as the normative basis for consumption. The research method used is qualitative research through a literature study approach by examining books, scientific journals, and relevant literature related to consumption, Islamic economics, and maqāṣid al-syarī‘ah. The results of the study show that consumption in Islamic economics is not only directed at fulfilling material needs, but must also meet the criteria of maslahah, namely being carried out proportionally, avoiding harm, being oriented towards collective welfare, and being in harmony with the objectives of sharia in protecting religion, life, reason, offspring, and property. However, in empirical reality, the consumption behavior of Muslim communities is still largely influenced by global consumerist culture and social status symbols, resulting in a gap between normative principles and actual practice. Therefore, strengthening the internalization of maslahah values in consumption behavior is important in order to achieve fair and sustainable welfare. This study is not supported by empirical data or field surveys to directly test the level of internalization of the principle of maslahah in the real consumption patterns of Muslim communities. Further empirical research is needed to quantitatively measure the normative-practical gap. In addition, internalizing these values requires concrete efforts through educational curricula, Islamic financial literacy campaigns, and synergistic public policies that encourage moderate and equitable consumption behavior.